2000
DOI: 10.1007/s12043-000-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electron irradiation on particle track etching response in polyallyl diglycol carbonate (PADC)

Abstract: In the present work, attempts have been made to investigate the modification in particle track etching response of polyallyl diglycol carbonate (PADC) due to impact of 2 MeV electrons. PADC samples pre-irradiated to 1, 10, 20, 40, 60, 80 and 100 Mrad doses of 2 MeV electrons were further exposed to 140 MeV ¾ Si beam and dose-dependent track registration properties of PADC have been studied. Etch-rate values of the PADC irradiated to 100 Mrad dose electron was found to increase by nearly 4 times that of pristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Etching needs energetic beams. Electron beams of 10 keV and up are currently used for polymer etching;45–47 this is 2 orders of magnitude larger than the energies used for this article.…”
Section: Resultsmentioning
confidence: 98%
“…Etching needs energetic beams. Electron beams of 10 keV and up are currently used for polymer etching;45–47 this is 2 orders of magnitude larger than the energies used for this article.…”
Section: Resultsmentioning
confidence: 98%
“…Although they accelerate the etching process, polymers like PMMA are generally etched with an acidic medium leading to very low etch track ratios @1-10. In a recent study on the polymer polyallyl diglycol carbonate (PADC) [9] it was found that etch-rate values of the PADC increase nearly fourfold if the polymer is irradiated with 100 Mrad dose of electrons at 2 MeV prior to the heavy ion irradiation. The etch tracks were created by 140 MeV Si ions.…”
Section: Type Of Membranementioning
confidence: 99%